Enhanced PRNGs based ACORN with Chaotic Map for Securing DICOM Image Encryption - T. Vijayakumar; M. Y. Mohamed Parvees (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Due to technological advances, medical and non-medical services are needed to provide the best teleradiology services to secure medical images. Primary issue is medical image secrecy. Conventional block and stream ciphers can’t encrypt large volumes of data because small files contain minimal data. The study aims in the direction of create a chaotic map based encryption algorithm to protect clinical images. The enhanced Pseudo Random Number Generators (PRNGs) Centered Additive Congruential Random Number [ACORN] generator, including the nonlinear dynamical method Logistic chaotic map, are utilized in this work to present a 24Bit colour DICOM image encryption technique. We use ACORN Generator to generate 8 (24Bit) random images in our recommended DICOM image encryption method. The equations of several Enhanced Chaotic Economic Maps are derived through replacing cosine and sine functions in the standard ECEM. High-reliability encryption is accomplished through careful analysis of the ECEMs’ Lyapunov exponents (proponents) and bifurcate nature. To protect patient privacy, 8-bit DICOM image pixels generated using enhanced Chaotic maps are swapped, chaotically distributed, and diffused using a variety of chaotic sequences. Scrambling is followed by a battery of security tests to prove the algorithm is sound; these include entropy, statistical, differential, key sensitivity, key space, noise attack, decryption effectiveness, and cropping.